دانپێدانان و ململانێی كۆمه‌ڵایه‌تی شیکردنەوەیەک بۆ تیۆرى ڕەخنەیی لاى ئه‌كسیل هۆنیث - فرج, د.ئارام على (Sulaimani Journal for Humanities, 2023)
This paper highlights on the theory of (struggle of recognition) by Axel Honneth as a representative of the third generation of the Frankfurt School. And that is through analyzing one of the most important concepts of his theory, the term recognition. In his book The Struggle for Recognition, and from a standpoint different from other thinkers, he analyzed the nature of conflict within human society. Honneth believes that, despite of the social, cultural, and political factors of conflict, the nature of the interpersonal relations in the interactive process has a big role in the conflict process, given that in this case, the parties become in a position of recognition or non-recognition with the other. All of this has a significant impact on the image that each one builds on his personal identity. To Honneth the basic principles of recognition are love, rights, and solidarity. Also, the process of disrespect, which is a violation of the body, denial of rights, and negative judgments on the social values of individuals, are the major obstacles to the process of recognition. These processes have a normative nature, and they have a central role in the conflict, and this is the point of distinction in Axel Honneth's theory, referred to in the results of this research paper.